Method and reaction device for preparing nanofiber-shaped lithium borohydride

Nanofibrous lithium borohydride was prepared by freeze-drying, which solved the problem of poor kinetic and thermodynamic performance of existing lithium borohydride materials under high temperature and high pressure, and achieved the improvement of efficient hydrogen storage performance and yield of lithium borohydride after nano-nomized.

CN119500015AActive Publication Date: 2025-02-25ZHEJIANG UNIV +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411689148.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing lithium borohydride materials require high temperature and high pressure during the desorption and rehydrogenation process, and have poor kinetic and thermodynamic performance, and have low yields during the nano-translation process and solvent residue problems, which affects the reduction of hydrogen release temperature.

Method used

Nanofibrous lithium borohydride was prepared by freeze-drying method. By mixing a mixed solution containing lithium borohydride and polar organic solvent with a refrigerant, vacuum-freeze-drying and room-temperature drying in an anhydrous and oxygen-free environment, the polar organic solvent and refrigerant were removed to obtain unloaded nanofibrous lithium borohydride.

Benefits of technology

It significantly reduces the hydrogen absorption and release temperature of lithium borohydride, improves its thermodynamic properties and reversible hydrogen storage capacity, has a large yield and good uniformity, and is suitable for the preparation of other hydrides.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500015A_ABST
    Figure CN119500015A_ABST
Patent Text Reader

Abstract

The invention discloses a method and a reaction device for preparing nanofiber-shaped lithium borohydride. The reaction device comprises a material tank which is arranged in the freeze-drying chamber and is provided with a valve, and a material for forming nanofiber-shaped lithium borohydride is filled in an inner cavity of a tank body of the material tank; the condenser is used for adjusting the temperature of the materials in the material tank to freeze-dry the materials and dry the materials at normal temperature; one end of the vacuum pump is connected with the freeze-drying chamber, and the vacuum pump is used for vacuumizing to form negative pressure in the freeze-drying chamber; and the inert gas supply equipment is connected with the freeze-drying chamber and is used for supplying inert gas to the freeze-drying chamber. The method comprises the following steps: transferring a solution obtained by mixing a mixed solution containing lithium borohydride and a polar organic solvent with a refrigerant into a reaction kettle, charging hydrogen into the reaction kettle, freezing to condense the solution in the reaction kettle, and sequentially carrying out vacuumizing low-temperature freeze drying and vacuumizing normal-temperature drying on the material in the reaction kettle in a water-free and oxygen-free environment to obtain the lithium borohydride / polar organic solvent. And removing the polar organic solvent and the refrigerant to obtain the nanofiber-shaped lithium borohydride.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nano material preparation, and in particular to a method and a reaction device for preparing nano fibrous lithium borohydride. Background Art

[0002] Nanotechnology refers to the science and technology of studying and applying materials at the nanoscale. Nanomaterials usually refer to materials with unique physical and chemical properties between 1 and 100 nanometers in size.

[0003] As a clean energy source, hydrogen does not produce carbon dioxide and is therefore seen as an important alternative to fossil fuels. However, the storage and transportation of hydrogen has always been one of the main obstacles to its widespread application.

[0004] Traditional hydrogen storage methods include high-pressure gaseous hydrogen storage and low-temperature liquid hydrogen storage, but both methods have high energy consumption, low storage density and safety issues.

[0005] To address these issues, researchers have turned to solid-state hydrogen storage materials that are able to store hydrogen at high density at lower pressures and temperatures. Metal hydrides, complex hydrides, and high surface area adsorbents such as carbon nanomaterials, zeolites, and metal-organic frameworks (MOFs) have been widely studied as alternative media.

[0006] Metal borohydrides are considered to be one of the most promising high-capacity candidate materials, with a weight density of up to 18wt% and reversible hydrogen storage capacity. However, their desorption temperature needs to be over 300°C, and re-hydrogenation requires 350°C and 35MPa. Therefore, the kinetics and thermodynamics of borohydrides need to be further improved.

[0007] One of the effective strategies is to reduce the particle size to the nanoscale. Nanomaterials have more significant kinetic regulation of lithium borohydride due to their high specific surface area and unique quantum effect, and can regulate its thermodynamics. The nano-sizing of lithium borohydride can be confined in a porous structure by melt impregnation and solution impregnation methods, and its hydrogen absorption and desorption temperature is significantly lower than that of the original material. By using the solvent evaporation strategy, LiBH4 nanoparticles with a size between 10.6 and 147.4 nm were obtained, and the main peak of stable dehydrogenation by polymethyl methacrylate was reduced from 488°C to 72°C. In order to maximize the reversible hydrogen storage capacity, people have tried to synthesize unloaded lithium borohydride nanoparticles. The hydrogen desorption of lithium borohydride nanoribbons with a width of 10-40nm begins at 60℃ [YPPang, YFLiu, MXGao, LZOuyang, JWLiu, H.Wang, M.Zhu, HGPan, A mechanical-force-driven physical vapour deposition approach to fabricating complex hydride nanostructures, Nature Commun., 2014, 5, 3519.]. The yield of unloaded lithium borohydride nanoparticles synthesized in the laboratory is low, and there is a problem of solvent residue, which makes it impossible to effectively reduce the hydrogen desorption temperature of lithium borohydride.

[0008] The freeze-drying method is used to prepare nanopowders, which have the advantages of regular powder shape, few hard agglomerates, small and uniform particle size, high chemical purity, good chemical uniformity, low sintering temperature, reliable preparation method, operability, and good repeatability. By preparing lithium borohydride by freeze-drying, it is expected to obtain unloaded nanofibrous lithium borohydride, further improve the thermodynamics and effective hydrogen storage capacity of lithium borohydride, and promote the application research of lithium borohydride hydrogen storage materials. Summary of the invention

[0009] The invention provides a method and a reaction device for preparing nanofiber-shaped lithium borohydride. The method is simple and easy to implement, has a large yield, and can be applied to other hydrides. The nanofiber-shaped lithium borohydride prepared by the invention has obvious length and good uniformity.

[0010] [1] A reaction device for preparing nanofibrous lithium borohydride, comprising:

[0011] A material tank with a valve placed in the freeze-drying chamber, wherein the inner cavity of the material tank contains a material for forming nano-fibrous lithium borohydride;

[0012] Condenser, used to adjust the temperature of the material in the material tank so that the material in the material tank can be freeze-dried and dried at room temperature;

[0013] A vacuum pump connected to the freeze-drying chamber at one end is used to evacuate the freeze-drying chamber to form a negative pressure environment;

[0014] The inert gas supply device connected to the freeze-drying chamber is used to supply inert gas to the freeze-drying chamber.

[0015] In some embodiments, in the reaction device for preparing nanofiber-shaped lithium borohydride, the material tank may be provided with a vent pipe connected to the inner cavity of the tank body, and the valve may be arranged on the vent pipe and away from the material tank body. This design keeps the valve away from the cold trap (condenser) to prevent the valve from failing in repeated alternation of hot and cold.

[0016] In some embodiments, in the reaction device for preparing nanofibrous lithium borohydride, the valve has the function of regulating gas flow, and the pressure in the tank can be adjusted to 0.1-1.5 MPa through the valve.

[0017] In some embodiments, in the reaction device for preparing nanofibrous lithium borohydride, the material tank may include a tank cover and a tank body, and the tank cover and the tank body may be sealed together. Further, the tank cover and the tank body are both threaded, and the tank cover and the tank body may be sealed by screws.

[0018] In some embodiments, in the reaction device for preparing nanofibrous lithium borohydride, the condenser may be located below the material tank.

[0019] In some embodiments, the reaction device for preparing nanofibrous lithium borohydride may further include a controller and a temperature sensor. The temperature sensor may be disposed on the material tank to monitor and reflect the temperature of the material tank. The controller may be connected to the temperature sensor and the condenser, and the controller may control the operation and running of the condenser according to the material tank temperature monitored and reflected by the temperature sensor.

[0020] In some embodiments, the other end of the vacuum pump of the reaction device for preparing nanofibrous lithium borohydride can be connected to an exhaust gas treatment device. Further, the exhaust gas treatment device can be a filter device, which can be filled with activated carbon and alcohol to filter and absorb organic gas extracted by the vacuum pump during the drying process. The filter device can be a barrel structure with an open top.

[0021] In some embodiments, in the reaction device for preparing nanofibrous lithium borohydride, the inert gas supply device can be a high-pressure inert gas bottle. Further, the high-pressure inert gas bottle can be connected to the freeze-drying chamber through a pressure reducing valve.

[0022] In the present invention, the inert gas may include at least one of nitrogen, a rare gas (such as argon, etc.), hydrogen, and a mixed gas of a rare gas.

[0023] [2] Use of the reaction device described in [1] in the preparation of nanofibrous lithium borohydride.

[0024] [3] A method for preparing nanofibrous lithium borohydride, comprising:

[0025] A mixed solution containing lithium borohydride and a polar organic solvent is mixed with a refrigerant, and the resulting solution is transferred to a ventilated reactor, hydrogen is filled into the reactor, and the solution in the reactor is frozen to condense into a solid, and then the material in the reactor is subjected to vacuum low-temperature freeze drying and vacuum room-temperature drying in an anhydrous and oxygen-free environment in sequence to remove the polar organic solvent and the refrigerant. After drying, an inert gas is filled into the reactor to normal pressure, and finally the nanofibrous lithium borohydride is taken out from the reactor in an inert atmosphere environment to obtain the nanofibrous lithium borohydride.

[0026] In some embodiments, in the method for preparing nanofibrous lithium borohydride, the polar organic solvent may include at least one of diethyl ether, methyl tert-butyl ether, tetrahydrofuran, oxirane, and ethylene glycol dimethyl ether, preferably diethyl ether. Lithium borohydride serves as a chain skeleton, and the polar organic solvent forms a protective coordination with the metal in the lithium borohydride to form a one-dimensional coordination polymer.

[0027] In some embodiments, in the method for preparing nanofibrous lithium borohydride, the refrigerant may include at least one of cyclohexane and n-hexane, preferably cyclohexane.

[0028] In some embodiments, in the method for preparing nanofibrous lithium borohydride, the concentration of lithium borohydride in the mixed solution containing lithium borohydride and a polar organic solvent may be 0.02 to 2 mmol / mL, preferably 0.18 to 0.2 mmol / mL.

[0029] In some embodiments, in the method for preparing nanofibrous lithium borohydride, the volume ratio of the polar organic solvent to the refrigerant can be 3:1 to 9, such as 3:1, 1:1, 1:3, etc., preferably 1:3. When the volume ratio continues to decrease, lithium borohydride will precipitate from the clear solution and become a suspension.

[0030] In some embodiments, in the method for preparing nanofibrous lithium borohydride, 1-10 bar of hydrogen can be charged into the reactor.

[0031] In some embodiments, the method for preparing nanofibrous lithium borohydride can be performed by freezing the solution in the reaction kettle with liquid nitrogen to condense the solution into a solid. The melting point of cyclohexane is 4-7°C, and it solidifies into a solid under the low temperature of liquid nitrogen freezing.

[0032] In some embodiments, in the method for preparing nanofibrous lithium borohydride, the vacuum low-temperature freeze-drying temperature may be -80 to -40°C (eg, -70°C), and the time may be 6 to 12 hours.

[0033] In some embodiments, in the method for preparing nanofibrous lithium borohydride, the vacuum drying at room temperature can be performed at a temperature of 20 to 50° C. and the drying time can be 6 to 12 hours.

[0034] Under low temperature (e.g. -67°C) and low pressure (vacuum) conditions, cyclohexane is directly sublimated from solid to gaseous state, and cyclohexane is removed. Since the temperature during the sublimation process is very low, the structure and properties of the nanomaterial are retained, and the time can be 6 to 12 hours. It is carried out at room temperature (e.g. 20°C to 30°C) and low pressure. This stage mainly removes the remaining cyclohexane and ether molecules, and the dried product is a loose one-dimensional structure, and the time can be 6 to 12 hours.

[0035] In the present invention, the inert gas may include at least one of nitrogen, a rare gas (such as argon, etc.), hydrogen, and a mixed gas of a rare gas.

[0036] In the present invention, the inert atmosphere environment may include at least one of a nitrogen atmosphere environment, a rare gas atmosphere environment, and a mixed atmosphere environment of hydrogen and a rare gas.

[0037] In some embodiments, the method for preparing nanofibrous lithium borohydride may use the reaction apparatus described in [1].

[0038] [4] Nanofibrous lithium borohydride prepared according to the method described in [3].

[0039] The diameter of the nanofiber-shaped lithium borohydride of the invention is adjustable within the range of 5 μm to 100 nm.

[0040] [5] Use of the nanofibrous lithium borohydride according to [4] in hydrogen absorption and desorption.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The invention adopts a physical method and utilizes low temperature to control the nucleation and growth of lithium borohydride, and can prepare high-purity nanofiber lithium borohydride with an adjustable diameter of 5 μm to 100 nm.

[0043] It has large yield and good universality for complex metal coordination hydrides.

[0044] The prepared lithium borohydride has high purity, small diameter and excellent hydrogen storage performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1It is a schematic structural diagram of a reaction device for preparing nanofibrous lithium borohydride according to the present invention.

[0046] Figure 2 for Figure 1 Schematic diagram of the vacuuming process of the reaction device shown.

[0047] Figure 3 for Figure 1 Schematic diagram of the gas return process of the reaction device shown.

[0048] Figure 4 This is a transmission electron microscope photograph of the product in Example 1 of the present invention.

[0049] Figure 5 X-ray diffraction patterns of lithium borohydride of Examples 1 to 4 of the present invention.

[0050] Figure 6 Fourier transform infrared absorption spectra of lithium borohydride of Examples 1 to 4 of the present invention and Comparative Example 1.

[0051] Figure 7 These are scanning electron microscope (SEM) photographs of the products of Example 1 (a, b), Example 2 (c, d), Example 3 (e, f) and Example 4 (g, h) of the present invention.

[0052] Figure 8 The temperature-programmed desorption spectra of lithium borohydride of Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention are shown.

[0053] Fig. 9 Optical photographs of lithium borohydride prepared in Example 1(a), Example 2(b), Example 3(c) and Example 4(d) of the present invention. DETAILED DESCRIPTION

[0054] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0055] The structural characteristics of the samples prepared in each case are characterized by X-ray diffraction patterns, Fourier transform infrared absorption spectra and energy dispersion spectra. Among them, the X-ray diffraction patterns are collected on a MiniFlex 600 X-ray diffractometer at 40 kV, 15 mA, 10°-90°, and 0.05° step length. The Fourier transform infrared absorption spectrum is collected on a German Bruker Tensor27 spectrometer in transmission mode, and the dry KBr and sample powder are mixed in a mass ratio of 200:1, and the applied pressure is 10 MPa.

[0056] The hydrogen desorption performance of the samples prepared in each case was characterized by temperature-programmed desorption spectra and volumetric hydrogen desorption curves. The programmed temperature desorption spectra were measured by a mass spectrometer and a homemade temperature control and heating device, with argon as the carrier gas at a flow rate of 20 mL / min and a heating rate of 2°C / min. The volumetric hydrogen desorption curve was measured by a homemade volumetric hydrogen desorption instrument, and non-isothermal hydrogen desorption tests were performed under vacuum conditions at a heating rate of 2°C / min.

[0057] For SEM measurements, the powders were dispersed on a conductive tape in a glove box and transferred to a Hitachi SU8010 SEM under argon protection using a custom-made scanning stage, operating at 5 kV. Transmission electron micrographs were taken on a Hitachi HT7700.

[0058] See also Figure 1 A reaction device for preparing nanofibrous lithium borohydride includes a vacuum pump 1, an exhaust gas treatment device 2, a controller 3, a freeze-drying chamber 4, an inert gas supply device 6, a material tank 7, a condenser 8 and a temperature sensor 9.

[0059] The material tank 7 includes a sealed tank cover and a tank body. The material tank 7 is provided with a vent pipe connected to the inner cavity of the tank body. The vent pipe is a slender iron pipe, on which a valve 10 is arranged, and the valve 10 is far away from the tank body of the material tank 7, so as to maintain the stability of the valve 10 during repeated alternation of hot and cold to prevent it from failing.

[0060] The material tank 7 is placed in the freeze-drying chamber 4, and the inner cavity of the material tank 7 is filled with material for forming nano-fibrous lithium borohydride.

[0061] The condenser 8 is located below the material tank 7 and is used to adjust the temperature of the material in the material tank 7 so that the material in the material tank 7 is freeze-dried and dried at room temperature.

[0062] The temperature sensor 9 is arranged on the material tank 7 to monitor and reflect the temperature of the material tank 7 .

[0063] The controller 3 is connected to the temperature sensor 9 and the condenser 8 , and the controller 3 controls the operation and running of the condenser 8 according to the temperature of the material tank 7 monitored and reflected by the temperature sensor 9 .

[0064] One end of the vacuum pump 1 is connected to the freeze-drying chamber 4 for evacuating the freeze-drying chamber 4 to form a negative pressure environment. The other end of the vacuum pump 1 is connected to the tail gas treatment device 2 .

[0065] The tail gas treatment device 2 is a filtering device, which adopts a barrel design with an open top and contains activated carbon and alcohol, and is used to filter and absorb the organic gas extracted by the vacuum pump 1 during the drying process.

[0066] The inert gas supply device 6 is a high-pressure inert gas bottle, which is connected to the freeze-drying chamber 4 via a pressure reducing valve 5 and is used to supply inert gas to the freeze-drying chamber 4 .

[0067] Use the above Figure 1 The reaction apparatus shown is evacuated, see Figure 2 The sealed material tank 7 is filled with materials for forming nano-fibrous lithium borohydride and is filled with hydrogen. The sample in the material tank 7 opens valve 10 under hydrogen pressure protection. In the freeze-drying chamber 4, the vacuum pump 1 is turned on to start vacuuming. The hydrogen pressure above the sample gradually decreases until it reaches a negative pressure state. The organic molecules contained in the material in the tank sublimate in a frozen state and enter the tail gas treatment device 2 through the vacuum pump 1. In this process, the sample does not come into contact with the air, and the vacuuming process under inert gas protection at low temperature is realized.

[0068] Use the above Figure 1 The reaction device shown is used for back-gassing, see Figure 3 , open the high-pressure inert gas bottle and adjust the pressure reducing valve 5 to 0.1MPa, and the inert gas enters the sample in the material tank 7. Turn off the vacuum pump 1, and the air pressure in the material tank 7 and the freeze-drying chamber 4 continues to rise until the freeze-drying chamber 4 reaches the atmospheric pressure. At this time, the internal and external air pressures are balanced, and the valve 10 of the material tank 7 is quickly closed. The sample is transferred to the glove box under the protection of inert gas and taken out.

[0069] The following examples 1 to 3 all adopt the above Figures 1 to 3 The reaction apparatus shown in the figure uses argon as the inert gas.

[0070] Example 1

[0071] Add 40 mg of lithium borohydride and 10 mL of ether to a flask and stir for 40 minutes. Transfer the lithium borohydride ether solution to a three-necked flask, add 30 mL of cyclohexane, and stir for 40 minutes. Transfer the solution to a ventilated reactor (i.e., material tank 7). Fill the reactor with 5 bar of high-purity hydrogen, place the reactor in liquid nitrogen, and freeze for 10 minutes. During the freezing process, the cyclohexane solution condenses into a solid. Move the reactor into a condenser 8 and dry it at -70°C under vacuum conditions for 12 hours. Turn off the refrigeration and continue drying under vacuum conditions for 6 hours. Use a high-pressure argon gas cylinder to fill argon into the freeze-drying chamber 4, and quickly close the reactor valve 10. Take out the product nanofibrous lithium borohydride (which can be recorded as LiBH4-40-10 ether-30 cyclohexane) in an argon atmosphere glove box and store it.

[0072] The transmission electron microscope photo of the nanofiber lithium borohydride product of this example is as follows Figure 4 shown.

[0073] Example 2

[0074] The only difference from Example 1 is that the amount of ether is changed to 20 mL and the amount of cyclohexane is changed to 20 mL, and the rest is the same, and the product nanofibrous lithium borohydride (which can be recorded as LiBH4-40-20 ether-20 cyclohexane) is obtained.

[0075] Example 3

[0076] The only difference from Example 1 is that the amount of ether is changed to 30 mL and the amount of cyclohexane is changed to 10 mL, and the rest is the same, and the product nanofibrous lithium borohydride (which can be recorded as LiBH4-40-30 ether-10 cyclohexane) is obtained.

[0077] Example 4

[0078] The only difference from Example 1 is that the amount of ether is changed to 40 mL and the amount of cyclohexane is changed to 0 mL (i.e., no cyclohexane is added), and the rest is the same, and the product lithium borohydride (which can be recorded as LiBH4-40-40 ether) is obtained.

[0079] Comparative Example 1

[0080] The commercial lithium borohydride after ball milling was used as a control sample. 1g of lithium borohydride was added to a ball milling jar with a volume of 180mL, the ball milling ratio was 120:1, the ball milling time was 12h, the rotation speed was 500 rpm, and after ball milling, the original lithium borohydride sample was scraped out in a glove box filled with argon atmosphere, and recorded as ball milled-LiBH4.

[0081] Figure 5 The results of X-ray diffraction are shown. The diffraction peak of nanofiber lithium borohydride is consistent with the standard diffraction peak of orthorhombic lithium borohydride; as the proportion of cyclohexane increases, the diffraction intensity gradually weakens.

[0082] Figure 6 The results of Fourier transform infrared absorption test are shown. The commercial lithium borohydride and nanofiber lithium borohydride have different absorption spectra at 2380, 2291, 2221 and 1122 cm -1 Characteristic BH vibrations are detected at.

[0083] Figure 7The figures show scanning electron microscope photos of Examples 1-4. It can be seen that the lithium borohydride prepared in Example 1 is in the form of nanofibers, with an average width of about 100nm and a length of more than 100μm; the lithium borohydride prepared in Example 2 is in the form of nanofibers, with an average width of about 300nm and a length of more than 100μm; the lithium borohydride prepared in Example 3 is in the form of nanofibers, with an average width of about 5μm and a length of about 40μm; the lithium borohydride prepared in Example 4 is in block form with a particle size of 100μm. As the amount of refrigerant cyclohexane added decreases, the diameter of the lithium borohydride fibers continues to increase. When the amount of refrigerant added is zero, the lithium borohydride becomes blocky. The addition of refrigerant not only reduces the size of lithium borohydride, but also changes the morphology of lithium borohydride into nanofibers.

[0084] The hydrogen release and hydrogen absorption properties of lithium borohydride samples were tested in a temperature-dependent hydrogen release and temperature-dependent hydrogen absorption mode. The test conditions were vacuum (initial vacuum degree was 1×10 -3 Torr) from room temperature to 600°C at a rate of 2°C / min and heated to 350°C at a rate of 1°C / min under 100 bar H2 pressure and kept at this temperature for 6 h. The degassing curve of the sample during heating was analyzed by mass spectrometry and fixed volume. The results are shown in Figure 8 . Figure 8 The figure is a comparison of the temperature-dependent hydrogen release curves of the nanofiber lithium borohydride samples prepared in Example 1, Example 2, and Example 3 and the ball-milled lithium borohydride sample prepared in Comparative Example 1. As can be seen from the figure, Figure 8 The starting dehydrogenation temperatures of Example 1, Example 2, and Example 3 are 100°C, 150°C, and 200°C, respectively, and the peak temperatures of the first step dehydrogenation are 350°C, 400°C, and 425°C, respectively. Figure 8 The peak temperature (433° C.) of the ball-milled lithium borohydride dehydrogenation of Comparative Example 1 was reduced by 83° C., 33° C., and 8° C., respectively, indicating that the nanofibers have improved the dehydrogenation performance of lithium borohydride.

[0085] Fig. 9 The optical photographs of lithium borohydride prepared in Examples 1 to 4 are shown. It can be seen that as the amount of cyclohexane added decreases, the volume of the lithium borohydride product decreases, and the particle size of the product is larger and more dense.

[0086] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A reaction device for preparing nanofibrous lithium borohydride, characterized in that: include: A material tank (7) is placed in the freeze-drying chamber (4) and is provided with a valve (10), wherein the inner cavity of the material tank (7) contains a material for forming nano-fibrous lithium borohydride; A condenser (8) is used to adjust the temperature of the material in the material tank (7) so that the material in the material tank (7) is freeze-dried and dried at room temperature; A vacuum pump (1) connected at one end to the freeze-drying chamber (4) for evacuating the freeze-drying chamber (4) to form a negative pressure environment; An inert gas supply device (6) connected to the freeze drying chamber (4) is used to supply inert gas to the freeze drying chamber (4).

2. The reaction device according to claim 1, characterized in that: The material tank (7) is provided with a vent pipe communicating with the inner cavity of the tank body, and the valve (10) is arranged on the vent pipe and away from the tank body of the material tank (7); The condenser (8) is located below the material tank (7); The reaction device further comprises a controller (3) and a temperature sensor (9); the temperature sensor (9) is arranged on the material tank (7) and is used to monitor and reflect the temperature of the material tank (7); the controller (3) is connected to the temperature sensor (9) and the condenser (8), and the controller (3) controls the operation and running of the condenser (8) according to the temperature of the material tank (7) monitored and reflected by the temperature sensor (9); The other end of the vacuum pump (1) is connected to the tail gas treatment device (2); the tail gas treatment device (2) is a filtering device, which contains activated carbon and alcohol and is used to filter and absorb the organic gas extracted by the vacuum pump (1) during the drying process; The inert gas supply device (6) is a high-pressure inert gas bottle, which is connected to the freeze-drying chamber (4) through a pressure reducing valve (5); the inert gas includes at least one of nitrogen, rare gas, hydrogen and a mixture of rare gas.

3. Use of the reaction device according to claim 1 or 2 in the preparation of nanofibrous lithium borohydride.

4. A method for preparing nanofibrous lithium borohydride, characterized in that: include: A mixed solution containing lithium borohydride and a polar organic solvent is mixed with a refrigerant, and the resulting solution is transferred to a ventilated reactor, hydrogen is filled into the reactor, and the solution in the reactor is frozen to condense into a solid, and then the material in the reactor is subjected to vacuum low-temperature freeze drying and vacuum room-temperature drying in an anhydrous and oxygen-free environment in sequence to remove the polar organic solvent and the refrigerant. After drying, an inert gas is filled into the reactor to normal pressure, and finally the nanofibrous lithium borohydride is taken out from the reactor in an inert atmosphere environment to obtain the nanofibrous lithium borohydride.

5. The method according to claim 4, characterized in that The polar organic solvent includes at least one of diethyl ether, methyl tert-butyl ether, tetrahydrofuran, hexyl oxide, and ethylene glycol dimethyl ether; The refrigerant includes at least one of cyclohexane and n-hexane; The concentration of lithium borohydride in the mixed solution containing lithium borohydride and a polar organic solvent is 0.02 to 2 mmol / mL; The volume ratio of the polar organic solvent to the refrigerant is 3:1-9; Fill the reactor with 1-10 bar of hydrogen; Liquid nitrogen is used to freeze the solution in the reactor into a solid; The vacuum low-temperature freeze-drying temperature is -80 to -40°C and the time is 6 to 12 hours; The vacuum drying is carried out at a temperature of 20 to 50°C and a time of 6 to 12 hours; The inert gas includes at least one of nitrogen, rare gas, hydrogen and a mixture of rare gas; The inert atmosphere environment includes at least one of a nitrogen atmosphere environment, a rare gas atmosphere environment, and a mixed atmosphere environment of hydrogen and rare gas.

6. The method according to claim 4 or 5, characterized in that: The reaction device according to claim 1 or 2 is used, and the material tank (7) is the ventilated reaction kettle.

7. Nanofibrous lithium borohydride prepared according to the method according to any one of claims 4 to 6.

8. The nanofibrous lithium borohydride according to claim 7, characterized in that: The diameter of the nanofiber-shaped lithium borohydride can be adjusted within the range of 5 μm to 100 nm.

9. Use of the nanofibrous lithium borohydride according to claim 7 or 8 in hydrogen absorption and desorption.

Citation Information

Patent Citations

  • High-capacity composite hydrogen storage material and hydrogen discharge method

    CN102442646A

  • Method for preparing metal coordination hydride nanorods

    CN103407964A

  • Metal complex hydride hydrate as well as preparation method and application thereof

    CN108946664A

  • Spray freeze dryer capable of controlling particle size of nano powder

    CN113289549A

  • Freeze dryer

    CN114777428A